PEMBELAJARAN MATEMATIKA YANG HUMANISTIK - Erik Santoso; Attin Warmi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
The problem of mathematics learning is a hot issue that continues to be a dailyfigure of mathematicians. Mathematics is still a concept or procedure that mustbe understood by the students through the learning done by the teacher in theclassroom. This problem is made into objects in a class rather than a subject inthe class. Therefore it is necessary to update the learning, which the concept isthe student as the subject, that is through the humanistic learning. Thehumanistic lessons of daring whose concepts must be related to the real worldand position the students to be creators in discovering the concept itself. Becausehumanistic learning has to be built a discovery process is part of this learning.Through learning that is able to be active in the learning process and able todevelop the ability to think creatively to be more dynamic. The creative thinkingprocess is important so that students are able to use that ability in everyday life.